The lived experiences of HIV-positive women in poverty - Msengana, Sweetlener Thobeka (Rhodes University, Faculty of Humanities, Department of Psychology, 2014)
The focus of this study was on the experiences of a small sample of local women who are HIVpositive and are living in poverty. The researcher was interested in exploring the psychological and social experiences of these women using Interpretive Phenomenological Analysis. This research aimed at giving these women a voice to express their first-hand, personal accounts of living with HIV in poverty. Data was analysed for meaningful units, which were interpreted inductively and hermeneutically, and categorised into super-ordinate themes. Six themes within the participants' experiences of living with HIV were determined, namely: (I) experiences of diagnosis, (2) disclosure experiences, (3) stigma, (4) ARV experiences, (5) experiences of social support and (6) poverty. This research found that after an HIV-positive diagnosis, most women experience a variety of emotional reactions. These reactions however seem to change overtime into positive acceptance of the HIV diagnosis. Most of the women in this study preferred to use partial disclosure than to fully disclose their HJV-positive status openly to families, friends and to their community. Reasons for not using full disclosure included fear of discrimination and stigma, which included a fear of being rejected or being blamed for their status and a fear of losing relationships. It was also evident from the findings that most of the women had experienced stigma directly and therefore partial disclosure was used as a coping mechanism to protect the self from further harm. It was also revealed that stigma not only has a negative impact on disclosure but also on social support and ARV experiences. Because ofHIV-related stigma, lack of social support was a struggle that almost all the women in this study had experienced. Lack of understandings about their medication also had a negative impact of the ARV experiences. Stigmas along with poverty are the major struggles that HIV -positive women have to deal with in their day to day living. The findings of this study reveal a need for further research in this experiential area as well as campaigns and education around issues such as stigma, medication, and emotional difficulties associated with HIV.
Keywords: HIV-positive women -- South Africa -- Grahamstown; HIV infections -- Psychological aspects -- South Africa -- Grahamstown; HIV infections -- Social aspects -- South Africa -- Grahamstown; Poor -- South Africa -- Grahamstown; Poverty -- Social aspects -- South Africa -- Grahamstown; Poverty -- Psychological aspects -- South Africa -- Grahamstown; Stigma (Social psychology) -- South Africa -- Grahamstown